Atividades com robótica educacional para as aulas de matemática do 6. ao 9. ano do ensino fundamental: utilização da metodologia LEGO® Zoom Education - Rodrigues, Willian dos Santos [UNESP] (2014)
This paper presents the qualitative result of four activities applied in the 6th to 9th grades of Elementary School and intend to design, implement and analyze a didactic sequence involving educational robotics and mathematics (with a focus on rational numbers). These activities were implemented in December 2014 in SESI school in Andradina, São Paulo state. The choice for the month of December was intended precisely so that students would use their knowledge and skills acquired during that school year. The importance of conducting this theme, together, comes the growing need of using technology that pervades the social environment in which the student is in; for education, and because the fractions are still a difficult paradigm to be assimilated by students, according to Silva (2006) and Demartini (2009). Based on LEGO® methodology, summarized in four words in order: Connect, Construct, Contemplate, and Continue, we used three assembly robots LEGO® Zoom to provide support to the resolutions of problem situations developed specifically for the idealization of this study. The research result showed that beyond that provided fun, it was instigated the curiosity of students to go through all four aforementioned actions, as consonant to problem situations contextualized, students, in group, easily assimilated the purpose of each activity